Butenolides from the Coral-Derived Fungus Aspergillius terreus SCSIO41404 - Qingyun Peng; Weihao Chen; Xiuping Lin; Jiao Xiao; Yonghong Liu; Xuefeng Zhou (Marine Drugs, 2022)
Five undescribed butenolides including two pairs of enantiomers, (+)-asperteretal G (1a), (−)-asperteretal G (1b), (+)-asperteretal H (2a), (−)-asperteretal H (2b), asperteretal I (3), and para-hydroxybenzaldehyde derivative, (S)-3-(2,3-dihydroxy-3-methylbutyl)-4-hydroxybenzaldehyde (14), were isolated together with ten previously reported butenolides 4–13, from the coral-derived fungus Aspergillus terreus SCSIO41404. Enantiomers 1a/1b and 2a/2b were successfully purified by high performance liquid chromatography (HPLC) using a chiral column, and the enantiomers 1a and 1b were new natural products. Structures of the unreported compounds, including the absolute configurations, were elucidated by NMR and MS data, optical rotation, experimental and calculated electronic circular dichroism, induced circular dichroism, and X-ray crystal data. The isolated butenolides were evaluated for antibacterial, cytotoxic, and enzyme inhibitory activities. Compounds 7 and 12 displayed weak antibacterial activity, against Enterococcus faecalis (IC50 = 25 μg/mL) and Klebsiella pneumoniae (IC50 = 50 μg/mL), respectively, whereas 6 showed weak inhibitory effect on acetylcholinesterase. Nevertheless, most of the butenolides showed inhibition against pancreatic lipase (PL) with an inhibition rate of 21.2–73.0% at a concentration of 50 μg/mL.